2013
DOI: 10.1007/s11274-013-1483-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of NAD aminohydrolase from Aspergillus oryzae NRRL447

Abstract: Aspergillus oryzae aminohydrolase free acid phosphodiesterase catalyzes nicotinamide adenine dinucleotide to deamino-NAD and ammonia. The enzyme was purified to homogeneity by a combination of acetone precipitation, anion exchange chromatography and gel filtration chromatography. The enzyme was purified 230.5 fold. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the purified enzyme showed a single protein band of MW 94 kDa. The enzyme displayed maximum activity at pH 5 and 40 °C with NAD as substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…5 ). This is similar to the optimal pH (5–7) of adenosine-phosphate deaminase of A. fumigatus (Yoshimune et al 2005 ), NAD deaminase produced by A. oryzae (Ali et al 2014 ). At pH 8.0, the deaminase loses 40 % of its activity as A. oryzae NAD deaminase, which had its optimum activity at pH 5 and abroad pH stability.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…5 ). This is similar to the optimal pH (5–7) of adenosine-phosphate deaminase of A. fumigatus (Yoshimune et al 2005 ), NAD deaminase produced by A. oryzae (Ali et al 2014 ). At pH 8.0, the deaminase loses 40 % of its activity as A. oryzae NAD deaminase, which had its optimum activity at pH 5 and abroad pH stability.…”
Section: Resultssupporting
confidence: 75%
“…It was found that the addition of EDTA (10 mM) to the reaction mixture did not inhibit enzyme activity indicating that NAD deaminase is not a metalloenzyme. This property closely resembles that of a nonspecific NAD aminohydrolase produced from A. oryzae (Ali et al 2014 ); whereas the enzyme was slightly activated by addition of Na + and K + , while inhibited by addition of Mn 2+ , Ag + , Hg 2+ , and Cu 2+ . In this concern, Yoshimune et al ( 2005 ) reported that the adenosine-phosphate deaminase produced by A. fumigatus was inhibited by 38 % in the presence of Cu 2+ (1 mM), while no significant enhancement of the enzyme activity was reported by Ba 2+ , Ca 2+ , Co 2+ , Fe 2+ , Mg 2+ , Mn 2+ , Ni 2+ , Sn 2+ , Zn 2+ and Fe 3+ .…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations